The Arabidopsis thaliana core splicing factor PORCUPINE/SmE1 requires intron-mediated expression - Varvara Dikaya; Nelson Rojas-Murcia; Ruben Maximilian Benstein; Wolf L. Eiserhardt; Markus Schmid (PLoS ONE, 2025)
Plants are prone to genome duplications and tend to preserve multiple gene copies. This is also the case for the genes encoding the Sm proteins of Arabidopsis thaliana (L). The Sm proteins are best known for their roles in RNA processing such as pre-mRNA splicing and nonsense-mediated mRNA decay. In this study, we have taken a closer look at the phylogeny and differential regulation of the SmE-coding genes found in A. thaliana, PCP/SmE1, best known for its cold-sensitive phenotype, and its paralog, PCPL/SmE2. The phylogeny of the PCP homologs in the green lineage shows that SmE duplications happened multiple times independently in different plant clades and that the duplication that gave rise to PCP and PCPL occurred only in the Brassicaceae family. Our analysis revealed that A. thaliana PCP and PCPL proteins, which only differ in two amino acids, exhibit a very high level of functional conservation and can perform the same function in the cell. However, our results indicate that PCP is the prevailing copy of the two SmE genes in A. thaliana as it is more highly expressed and that the main difference between PCP and PCPL resides in their transcriptional regulation, which is strongly linked to intronic sequences. Our results provide insight into the complex mechanisms that underlie the differentiation of the paralogous gene expression as an adaptation to stress.